2018
DOI: 10.1103/physrevlett.120.215301
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Time Quasicrystal and Its Transition to a Superfluid Time Crystal

Abstract: We report experimental realization of a quantum time quasicrystal and its transformation to a quantum time crystal. We study Bose-Einstein condensation of magnons, associated with coherent spin precession, created in a flexible trap in superfluid ^{3}He-B. Under a periodic drive with an oscillating magnetic field, the coherent spin precession is stabilized at a frequency smaller than that of the drive, demonstrating spontaneous breaking of discrete time translation symmetry. The induced precession frequency is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
127
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(130 citation statements)
references
References 51 publications
1
127
0
2
Order By: Relevance
“…A crystalline structure in time is related to the periodic dynamics of a system. It has been shown that periodically driven quantum many-body systems can spontaneously self-reorganize their motion and start moving with a period different from the period of the driving [12][13][14] (see also [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]). This kind of spontaneous formation of a new crystalline structure in time is dubbed discrete or Floquet time crystals and has been already realized experimentally [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…A crystalline structure in time is related to the periodic dynamics of a system. It has been shown that periodically driven quantum many-body systems can spontaneously self-reorganize their motion and start moving with a period different from the period of the driving [12][13][14] (see also [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]). This kind of spontaneous formation of a new crystalline structure in time is dubbed discrete or Floquet time crystals and has been already realized experimentally [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…(6). We emphasize that, differently from previous works [36], we believe the presence of two incommensurate frequencies to be a necessary but not sufficient ingredient for the definition of a DTQC [40]. Rather, in analogy with the more established notion of DTC, we judge essential the presence of the robust subharmonic peak, which is a genuine many-body feature.…”
mentioning
confidence: 64%
“…This requires that the non-zero Floquet quasi-frequency of the long life modes takes the form q w = m n j Im with integer n=2, 3, K and = ¼ m n 1, 2, , 1. In general, the non-zero Floquet quasifrequency can be incommensurate with the drive, this would lead to the so called time quasi-crystal [26], but this is beyond our scope of study in this work.…”
Section: Floquet Analysis 41 Floquet Basicsmentioning
confidence: 99%